Positive Emotional Involvement as a Mediator of Visual Merchandising and Impulsive Buying on Shopee in Banda Aceh - Erdin, Muhammad Farhan; Sitepu, Novi Indriyani (Universitas Syiah Kuala, 2025)
This study examines the mediating role of positive emotional involvement in the relationship between visual merchandising and impulsive buying among Shopee users in Banda Aceh. In the era of rapidly growing e-commerce, visual merchandising has become a crucial strategy to attract consumers attention and influence unplanned purchasing decisions. However, consumer behavior is not solely shaped by external stimuli but also by emotional factors that drive responses to online shopping experiences. Using a quantitative approach, data were collected from 105 respondents through purposive sampling, and mediation regression analysis was performed using SPSS. The findings indicate that visual merchandising has a significant effect on impulsive buying and that positive emotional involvement serves as a full mediator in this relationship. This means that consumer emotions play a central role in transforming the appeal of visual displays into actual purchase behavior. The study provides both theoretical and practical contributions, emphasizing the importance of emotional engagement in strengthening marketing effectiveness within e-commerce platforms.